AAV8 gene therapy for mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) in a patient's liver maintained ex situ for 9 days - Teresa Brevini; Lisa Swift; Helen Reynolds; John Ong; Richard Stopforth; Yogeshkumar Malam; Harry Spiers; AnnaPaterson; Adam Duckworth; Arthur Kaser; Vassillis Kosmoliaptsis; Ramon Marti; et al. (Clinical Medicine)
Introduction: Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare genetic disorder caused by mutations in TYMP.1 This results in nucleoside accumulation, mitochondrial damage and progressive gastrointestinal and neurological dysfunction leading to cachexia and death before 40 years. No established treatment exists. Liver transplantation restores nucleoside levels, but is not indicated in all patients (eg, severely malnourished patients) and is associated with complications.1 Adeno-associated virus (AAV) gene therapy offers an attractive therapeutic alternative, which is already clinically approved for other genetic diseases and has been successful in MNGIE animal models.2 Nevertheless, it has not been tested in human and, because of the rarity of MNGIE (<200 cases described), obtaining sufficient numbers for robust AAV trials is challenging. Ex situ machine perfusion (ESMP) maintains organs in near-physiological conditions before transplantation and is emerging as a new avenue to trial novel therapies in the liver with the potential to address this limitation.3–7 However, until now only donor livers, not affected by disease, have been used for these studies, preventing testing of treatment efficacy. Our aim was to test AAV gene therapy for MNGIE in the explanted liver of a patient transplanted for this disease, which was maintained on ESMP. Materials and Methods: A 34-year-old patient with MNGIE underwent liver transplantation as enzyme replacement therapy. The explanted liver was divided into anatomical right and left lobe and perfused ex situ using two XVIVO LiverAssist devices for 9 days. Nucleoside levels in the perfusate were measured with mass spectrometry. An AAV serotype 8 encoding for TYMP was used at a dose of 1011 viral genomes/kg of liver. PCR, qPCR and immunofluorescence for TYMP were used to assess treatment efficacy. Perfusion parameters (flow and pressure), biochemistry (ALT, pH and glucose) and histology were used to assess treatment toxicity. Results: Within 24 h of perfusion, nucleosides accumulated in the perfusate, recapitulating key features of MNGIE. Subsequently, one lobe received AAV8-TYMP, while the other served as an internal control and received carrier injection. The viral vector was taken up by hepatocytes and TYMP expression was restored in the treated lobe within 3 days. Importantly, AAV8-TYMP treatment resulted in clearance of nucleoside from the perfusate, which recapitulated nucleoside clearance from the patient’s blood following liver transplant. Furthermore, long-term ESMP of the two liver lobes revealed no evidence of hepatotoxicity following AAV8 gene therapy, including normal ALT. Conclusion: Our report provides the first demonstration of the safety and efficacy of AAV gene therapy for MNGIE in a human liver, paving the road for clinical trials. We describe the first UK perfusion of a patient's organ, shifting the paradigm of using ESMP exclusively for donor livers to patient explanted pathological livers as a novel platform for drug testing. Using ESMP to test promising novel therapeutic candidates could offer an intermediate platform bridging the gap between animal studies and clinical trials. Finally, our study provides proof of principle for the efficacy of AAV gene therapy for treating diseased livers on ESMP, which could be applied to various other liver diseases.